2014
DOI: 10.1159/000369117
|View full text |Cite
|
Sign up to set email alerts
|

17q21.31 Microdeletion: Brain Anomalies Leading to Prenatal Diagnosis

Abstract: Ultrasound examination performed on a 36-year-old woman at 33 weeks of gestation showed the presence of isolated and bilateral ventriculomegaly in the fetus. Array-based comparative genomic hybridization (array-CGH) performed on uncultured amniocytes at 35 weeks of gestation revealed a 17q21.31 microdeletion. After genetic counseling, the pregnancy was terminated at 37 weeks of gestation. At autopsy, the fetus displayed facial dysmorphic features and triventricular ventriculomegaly. To our knowledge, this is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Deletions of this region or KANSL1 mutations lead to Koolen‐de Vries syndrome (KDVS, MIM 610443), characterized by intellectual disability, hypotonia, friendly demeanor, recognizable dysmorphic features, and less frequently cardiac or genitourinary anomalies and seizures. One of our fetal cases was reported (Egloff et al, ) It is noteworthy that a CCM is observed in 20% of deleted patients, while KDVS patients with KANSL1 mutations do not present a CCM (Zollino et al, ; Koolen et al, ). This suggests that another gene within the deletion might be responsible for this endophenotype.…”
Section: Resultsmentioning
confidence: 86%
“…Deletions of this region or KANSL1 mutations lead to Koolen‐de Vries syndrome (KDVS, MIM 610443), characterized by intellectual disability, hypotonia, friendly demeanor, recognizable dysmorphic features, and less frequently cardiac or genitourinary anomalies and seizures. One of our fetal cases was reported (Egloff et al, ) It is noteworthy that a CCM is observed in 20% of deleted patients, while KDVS patients with KANSL1 mutations do not present a CCM (Zollino et al, ; Koolen et al, ). This suggests that another gene within the deletion might be responsible for this endophenotype.…”
Section: Resultsmentioning
confidence: 86%
“…Such genes are themselves very polymorphic [60] and the different alleles allow for a fine-tuning of the immunological response. Locus 17q21.31 contains several genes potentially implicated in neurodegenerative diseases [61] and strongly tied to other dementias [62, 63]. Due to its structure, it is prone to genomic rearrangements [64, 65] whose evolutionary meaning is not yet clear.…”
Section: Resultsmentioning
confidence: 99%
“…The central nervous system abnormalities include ventriculomegaly, anomalies of corpus callosum, white matter abnormalities, etc. (Egloff et al, 2014). None of these structural malformations were found in our patients.…”
Section: Discussionmentioning
confidence: 99%